METHODS OF CONDUCTING PHYSICAL EDUCATION ACTIVITIES IN THE DEVELOPMENT OF PRESCHOOL CHILDREN - Amirkanovich, Abdukarimov Nurmakan (PT. Antis International Publisher, 2024)
In this article, information on the methods of organizing physical education classes by educators in preschool educational institutions is applied